Lutas na Educação física escolar: conhecimento e práticas docentes na região norte do país. - Serra, Flávio da Silva (Universidade Federal do Tocantins, 2021)
The performance of physical exercises as a resource to improve the health and quality of life of people are already well consolidated in literature, among them, it stands out to the struggles that despite its imprecise origin, is present in the life of the human being since prehistory and has gained space in Physical Education, and can be inserted in various ways in the stages of schooling, since we can observe them in many jokes already practiced in the daily lives of students. The implementation of school fights is guided by the National Curricular Parameters (PCN's) and becomes relevant for providing students with a broader knowledge in order to develop their motor, cognitive and affective-social aspect, thus aiming at quality teaching. Therefore, the objective of this study was to investigate the knowledge and teaching practices of teachers in the city of Tocantinópolis/TO about the application of fights in school physical education, to verify if they had access to any content that addressed the issue of fights in the graduation process, to identify if there was some complementary training to teach the content of fights and also if there was insertion of fights in the classes and to verify the availability of spaces and materials suitable for carrying out these activities in schools. In this sense, we did a study of the historical contextualization of the fights and also the application of interview questionnaires with Physical Education teachers in the municipality of Tocantinópolis/TO, where we could observe that there are still many challenges to be faced by Physical Education teachers in schools, from their own qualification in the area of fights, an appropriate place for their practices, as well as the resistance of students and some parents about the practices of fights. In face of this we could notice that it is necessary that the classes of fights are applied correctly, emphasizing their importance and the true meaning of the fight.